Dynamic Monitoring of Immunoinflammatory Response Identifies Immunoswitching Characteristics of Severe Acute Pancreatitis in Rats - Zhuang, Qian; Huang, Liqiang; Zeng, Yue; Wu, Xu; Qiao, Gan; Liu, Minghua; Wang, Lulu; Zhou, Yejiang; Xiong, Yuxia (Frontiers in Immunology, 2022)
Background: Immune dysfunction is the main characteristic of severe acute pancreatitis (SAP), and the timing of immune regulation has become a major challenge for SAP treatment. Previous reports are conflicting about the time point at which the immune status of SAP changed from excessive inflammatory response to immunosuppression (hypo-inflammatory response). Purposes: The aim of this study is to explore the immunological dynamic changes of the SAP rats from the perspective of intestinal mucosal immune function, and to determine the immunoswitching point from excessive inflammatory response to immunosuppression. Methods: Retrograde injection of sodium taurocholate into the pancreaticobiliary duct was applied to establish SAP model in rats. The survival rate and the activities of serum amylase and pancreatic lipase in SAP rats were measured at different time points after model construction. The pathological changes of the pancreas and small intestines were analyzed, and the levels of intestinal pro- and anti-inflammatory cytokines and the numbers of intestinal macrophages, dendritic cells, Th1, Th2, and T regulatory cells were assessed. Meanwhile, the SAP rats were challenged with Pseudomonas aeruginosa (PA) strains to simulate a second hit, and the levels of intestinal inflammatory cytokines and the numbers of immune cells were analyzed to confirm the immunoswitching point. Results: The time periods of 12-24 h and 48-72 h were the two death peaks in SAP rats. The pancreas of SAP rats showed the self-limiting pathological changes, and the switching period of intestinal cytokines, innate and adaptive immunity indexes occurred at 24-48 h. It was further confirmed that 48 h after SAP model construction was the immunoswitching point from excessive inflammatory response to immunosuppression. Conclusion: The SAP rats showed the characteristics of intestinal mucosal immune dysfunction with 48 h after SAP model construction determined as the immunoswitching point from excessive inflammatory response to immunosuppression. The results are of great significance for optimizing the timing of SAP immune regulation.